Pemodelan Regresi Data Panel pada IPM di Sulawesi Selatan - Zakiyah Mar'ah; Ruliana Ruliana; Ansari Saleh Ahmar; Zulkifli Rais (Program Studi Statistika Fakultas MIPA UNM, 2023)
HDI is an important indicator to measure success in efforts to build the quality of human life (community/population). HDI can determine the rank or level of development of a region/country. For Indonesia, HDI is strategic data because apart from being a measure of government performance, HDI is also used as an allocator for determining the General Allocation Fund (DAU). The development of HDI in Indonesia has always increased from year to year. In South Sulawesi, the HDI has increased significantly in the last 10 years. Where in 2012 the HDI of South Sulawesi was at 67.26 to 72.82 in 2022. This is measured based on three essential aspects, namely longevity and healthy living, knowledge, and a decent standard of living. Along with HDI, other indicators also show an increase from year to year. To find out how much these variables affect the increase in HDI during the 2018-2022 period, the panel data regression method is used which is a combination of time series data and cross section data. The regression model that is suitable for South Sulawesi HDI data from 2018-2022 is a panel data regression model with one-way random effects, namely individual effects. The model is written as follows IPM=(-1.9360e+01) + (1.0734e+00) UHH + (1.4014e-03) PPK + e